Comparison of simulation debriefs with traditional needs assessment methods: a qualitative exploratory study in a critical care community setting. Issue 10 (8th October 2018) - Sarti, Aimee J; Ajjawi, Rola; Sutherland, Stephanie; Landriault, Angele; Kim, John; Cardinal, Pierre
Abstract : Objective: To better understand the potential of a needs assessment approach using qualitative data from manikin-based and virtual patient simulation debriefing sessions compared with traditional data collection methods (ie, focus groups and interviews). Design: Original data from simulation debrief sessions was compared and contrasted with data from an earlier assessment of critical care needs in a community setting (using focus groups and interviews), thus undertaking secondary analysis of data. Time and cost data were also examined. Debrief sessions were coded using deductive and inductive techniques. Matrices were used to explore the commonalities, differences and emergent findings across the methods. Setting: Critical care unit in a community hospital setting. Results: Interviews and focus groups yielded 684 and 647 min of audio-recordings, respectively. The manikin-based debrief recordings averaged 22 min (total=130 min) and virtual patient debrief recordings averaged 31 min (total=186 min). The approximate cost for the interviews and focus groups was $13 560, for manikin-based simulation debriefs was $4030 and for the virtual patient debriefs was $3475. Fifteen of 20 total themes were common across the simulation debriefs and interview/focus group data. Simulation-specific themes were identified, including fidelity (environment, equipment and psychological) and the multiple roles of the simulation instructor (educative, promoting reflection and assessing needs). Conclusions: Given current fiscal realities, the dual benefit of being educative and identifying needs is appealing. While simulation is an innovative method to conduct needs assessments, it is important to recognise that there are trade-offs with the selection of methods.